The Relationship Between Stress Levels and the Risk of Premature Birth in Pregnant Women at the Saritani Community Health Center (UPTD) - Afreciami Kartika; Widia Shofa Ilmiah (Jurnal Siti Rufaidah, 2025)
Pregnancy is one of the most significant phases in a woman's life, involving both physical and psychological changes. One of the psychological factors that often arise during pregnancy is stress. Stress during pregnancy can affect both maternal health and fetal development, and may even increase the risk of preterm birth. This study aims to analyze the relationship between stress levels in pregnant women and the risk of preterm birth at the UPTD Puskesmas Saritani. The study uses a quantitative design with a descriptive approach, where data was collected from 104 pregnant women screened using the Edinburgh Postnatal Depression Scale (EPDS) and birth status recorded in the medical records of the health center. The results showed that pregnant women who experienced stress had a higher likelihood of preterm birth compared to those who did not experience stress. This study is expected to contribute to the understanding of the impact of stress on maternal and fetal health and provide a foundation for the development of health programs to detect and manage stress in pregnant women, ultimately reducing preterm birth rates.